Narcotic use in patients following a traumatic injury - Bethea, PharmD, BCPS, BCCCP, Audis; Samanta, MS, Damayanti; Amodeo, MD, Kellie (Journal of Opioid Management, 2020)
Objective: To determine the incidence and factors associated with long-term opioid use in trauma patients who were previously opioid-naïve. Design: A retrospective cohort study. Setting: Level I Trauma Center. Patients, participants: Patients admitted to the study institution between January and October 2016 following traumatic injury. Trauma patients were linked with data from the state’s Controlled Substance Monitoring Program (CSMP) database regarding controlled substance use. Main outcome measure(s): Long-term use (LTU) of opioid medications following hospital discharge. Long-term use was defined as 4 weeks and above based on the Centers for Disease Control and Prevention’s recommendation that opioid therapy should not be continued for > 4 weeks without a clinician evaluating the risk versus benefits of continued therapy. Results: The incidence of LTU in previously naïve patients was 46 percent. Preexisting psychiatric illness (OR = 4.764, 95 percent CI = 1.592-14.260, p = 0.005) and prior controlled substance use (OR = 4.155, 95 percent CI = 1.903-9.072) were determined to be predictors for LTU. Patients with psychiatric comorbid conditions were almost five times more likely to be in the LTU group. Those with prior controlled substance use history were four times more likely to be in the LTU group. Conclusions: These findings provide initial insight concerning the LTU of opioids in previously naïve patients. Application of these data may facilitate early identification of patients at risk for LTU following traumatic injury and serve to influence prescribing practices in these at-risk individuals.